Can you greet the whole wide world? : 12 common phrases in 12 different languages - Evans, Lezlie (Houghton Mifflin, 2006)
Introduces young readers to common phrases such as "good morning", "thank you", and "please" in German, Hebrew, Spanish, Arabic, Russian, Hindi, Chinese, Zulu, Japanese, Italian, French, and Portuguese.